Conditions for Instability of an Invariant Toroidal Manifold of a Discrete Dynamical System in a Banach Space - Slyusarchuk, V. V. (Ukrains’kyi Matematychnyi Zhurnal, 2001)
We obtain conditions for the instability of an invariant toroidal manifold of a discrete dynamic system.